Medical law: professionals' training prospects in Ukraine - Tsekhmister Yaroslav; Lysenko Oleksandra (Borys Grinchenko Kyiv Metropolitan University, 2017)
In order to implement educational programs for sustainable development among doctors who are representatives of one of the most socially important professions, it is necessary to increase the level of their legal culture, in particular in the sphere of relations arising during the medical activity. The content of education for sustainable development should be relevant to the needs of the modern society with the emphasis on both cognitive and non-cognitive aspects of learning. Thus, it is due to the programs of education for sustainable development that include global civil education on the issues of peace, human rights, as well as intercultural and international relations, the need of the population for the knowledge, skills, values and attitude is satisfied,which is necessary for the adoption of reasonable decisions and active participation in solving both local and global problems of our time. These provisions are of particular importance given the characteristics of the medical profession. After all, health care, as one of the most socially meaningful fields of activity, is associated with the emergence of specific legal relations regulated by regulatory and legal acts. In our opinion, in order to create the preconditions for further development and strengthening of the social significance of medical law, it is necessary to amend the List of branches of knowledge and specialties, which are training applicants for tertiary education, approved by the decision of the Cabinet of Ministers of Ukraine dated April 29, 2015, No.266, namely, to make an addition of a list of names of specialties in the field of knowledge 08 «Law» with the specialty «Medical Law». The proposed innovation will not only provide opportunities for the development of a given legal field, but will also provide the opportunity to introduce tertiary education programs for the simultaneous training for two specialties in the fields of knowledge 22 «Health» and 08 «Law», which, in our opinion, will contribute to increase the level of professional competence of medical workers.